A RARE CASE OF HYPOGONADOTROPHIC HYPOGONADISM IN AN ADOLESCENT FEMALE - Mohamad, Aimi Fadilah; Hatta, Sharifah Faradila Wan Muhamad; Shah, Fatimah Zaherah Mohamed; Warman, Nuraini Eddy; Zainordin, Nur Aisyah; Awang, Mohd Hazriq; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Hypogonadotrophic hypogonadism refers to hypogonadism due to deficiency in gonadotrophins. Reduced levels of gonadotrophins [luteinizing hormone (LH) and follicle-stimulating hormone (FSH)] results in lack of stimulation for estradiol production leading to amenorrhea, absent breast and uterine development in females. The underlying gonadotrophin deficiency is commonly due to lesions in the pituitary or hypothalamus but can be due to rare genetic causes. RESULTS We present a case of a 16-year-old girl who presented with primary amenorrhea and lack of secondary sexual characteristics. She had no underlying medical conditions and denied any other symptoms. There were no excessive stress or weight changes noted. Both her sister and mother attained menarche at 14 years old. On examination, her BMI was 25 kg/m2 and height was 151 cm (mid-parental height was 155 cm). There were no syndromic features, no hirsutism, and no features suggestive of virilization. External genitalia examination revealed an infantile labia with intact introitus. Tanner staging for breast was 2/5 and for pubic hair 1/5. Her hormonal profile showed hypogonadotrophic hypogonadism. Her estradiol levels were undetectable at <36.7 pmol/L. LH was 1.14 IU/L (NR 2.4–12.6) and FSH was 2.61 IU/L (NR 3.5–12.5). Testosterone level was also low at 0.1 nmol/L (NR 0.3–2.4). Other anterior pituitary hormones were normal. Her bone age was delayed at 14 years compared to her chronological age of 16 years. Karyotyping showed female genotype of 46XX. Pelvic MRI showed hypoplastic uterus with normal vagina and ovaries. Pituitary MRI revealed normal pituitary gland. There were no obvious causes for her condition. CONCLUSION The diagnosis for this case is Idiopathic Hypogonadotrophic Hypogonadism (IHH). This is a diagnosis of exclusion. There may be rare genetic defects affecting neurons in the hypothalamus and/or pituitary responsible for this presentation and genetic testing can be helpful.